Effect of weather conditions, substrate pH, biochar amendment and plant species on two plant growth-promoting microbes on vegetated roofs and facades - Long Xie; Sari Timonen; Alan C. Gange; Kirsi Kuoppamäki; Marleena Hagner; Susanna Lehvävirta (Heliyon, 2022)
Background: Vegetated building envelopes (VBEs), such as vegetated roofs and facades, are becoming more frequent in urban planning nowadays. However, harsh growing conditions restrain the application of VBEs. Plant growth-promoting microbes (PGPMs) might help ease the stresses, but first, it is necessary to investigate how to ensure their survival and growth under VBE conditions. Methods: We conducted three experiments to test the impact of various factors on the microbial populations of inoculated PGPMs in VBEs, a mycorrhizal fungus Rhizophagus irregularis and a bacterium Bacillus amyloliquefaciens. The first experiment was conducted by inoculating the two PGPMs separately in Sedum roof plots, and the microbial populations associated with Poa alpina was monitored for two consecutive years under local weather conditions. The second experiment was conducted in a laboratory testing the effect of substrate pH (substrates collected from balcony gardens) on R. irregularis population associated with Trifolium repens and Viola tricolor. The third experiment was conducted on a meadow roof testing the effect of biochar amendment on R. irregularis population associated with Thymus serpyllum and Fragaria vesca. Results: In the first experiment, Bacillus was found to associate with P. alpina, but Rhizophagus wasn't. Yet, the fungus induced high Bacillus population density in the Rhizophagus treated plots in the first year. In the second experiment, Rhizophagus abundance in T. repens was higher in the neutral substrate (6–6.5), while V. tricolor was more colonized in acidic substrate (5–5.5), suggesting an important interactive effect of substrate pH and plant species on Rhizophagus abundance. The third experiment suggested a negligible impact of biochar amendment on Rhizophagus abundance for both host plants. Conclusion: Three experiments demonstrate that PGPM inoculation on VBEs is feasible, and various factors and interactions affect the PGPM populations. This paper provides reference and inspiration for other VBE ...